Prospective, randomized comparative evaluation of a novel hands-on endourology training curriculum - Waldbillig, Frank; Rohr, Lennard von; Nientiedt, Malin; Neuberger, Manuel; Wessels, Frederik; Hardenberg, Jost von; Westhoff, Niklas Christian; Wuhrer, Anne; Pechlivanidou, Ioanna; Miernik, Arkadiusz; Michel, Maurice Stephan; Kriegmair, Maximilian; et al. (Urologia internationalis, 2023)
Introduction: The aim of this randomised prospective trial was to evaluate a novel hands-on endourological training programme (HTP) and compare it to the standard endourological colloquium (SC). Methods: A new HTP was created based on a sequence of theoretical, video-based, and practical elements emphasising contemporary teaching methods. An existing SC in which live endourological operations were attended served as a comparison. Medical students were enrolled in a ratio of 1:2 (SC:HTP). Objective knowledge questionnaires (5 questions, open answers) and subjective Likert-type questionnaires (rating 1-3 vs. 4-5) were used for evaluation. Primary endpoint was urological knowledge transfer; secondary endpoints were learning effects, progression, and urological interest. Results: 167 students (SC n = 52, HTP n = 115) were included. The knowledge assessment showed a significant increase in knowledge transfer benefitting the HTP on all 5 surveyed items (mean: n = 4/5/4/3/2 vs. n = 2/3/1/1, p < 0.0001). Interest and duration of the course were rated significantly more positively by HTP students (100.0/95.0% vs. 85.0/70.0%, p < 0.0001). The HTP students were significantly more confident in performing a cystoscopy independently (HTP 43.5% vs. SC 11.5%, p < 0.0001) and significantly claimed more often to have gained interdisciplinary and urological skills during the course (HTP 90.0/96.5% vs. SC 23.1/82.7%, p < 0.0001/p = 0.003). HTP students were also more likely to take the course again (HTP 98.2% vs. SC 59.6%, p < 0.0001). Conclusion: Modifying endourological teaching towards hands-on teaching resulted in stronger course interest, greater confidence regarding endourologic procedures, and significantly increased urologic knowledge transfer.
Online veröffentlicht: 8. Dezember 2022
Gesehen am 06.08.2024